2019
DOI: 10.1371/journal.pone.0220570
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in non-small cell lung cancer patients with an ultra-high expression of programmed death ligand-1 treated using pembrolizumab as a first-line therapy: A retrospective multicenter cohort study in Japan

Abstract: Background Pembrolizumab is currently approved as a first-line therapy for advanced non-small cell lung cancer (NSCLC) patients with a programed death ligand-1 (PD-L1) expression ≥50%. However, the association between the efficacy of pembrolizumab and PD-L1 expression levels in patients with PD-L1 expression ≥50% has not been fully elucidated. Methods We retrospectively analyzed patients with advanced NSCLC and a PD-L1 tumor proportion score (TPS) of ≥50% who received p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 23 publications
(30 reference statements)
4
10
0
Order By: Relevance
“…High rates of PD reaching 28.7% among French patients [7] and 24.2% among Japanese patients [8] have led to early PD in the population. The early PD rate was reported to be similar to that of populations with ultrahigh PD-L1 expression of 90 to 100% [9]. This finding contradicts another report [10].…”
Section: Discussionmentioning
confidence: 70%
“…High rates of PD reaching 28.7% among French patients [7] and 24.2% among Japanese patients [8] have led to early PD in the population. The early PD rate was reported to be similar to that of populations with ultrahigh PD-L1 expression of 90 to 100% [9]. This finding contradicts another report [10].…”
Section: Discussionmentioning
confidence: 70%
“…Seventeen RCT studies reported progression-free survival (PFS) from up to 3 years patient follow-up 30–41 43 44 93–95. Fifty-two observational studies with short-term follow-up reported PFS 47–58 62–71 73–75 77–84 86–89 91 92 96–103. Heterogeneity in the meta-analysed studies tended to be high; the I 2 statistics for short-term follow-up studies of nivolumab and pembrolizumab were 69% and 91%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, PD-L1 expression in the tumor microenvironment will reduce the T cell-based antitumor immune response [10,23,24]. Two anti-PD-1 monoclonal antibodies (nivolumab and pembrolizumab) [25][26][27] and three anti-PD-L1 monoclonal antibodies (atezolizumab, avelumab, and durvalumab) [28][29][30] have been approved by the US Food and Drug Administration (FDA) for treating cancers, for example, melanoma, nonsmall cell lung cancer, and renal cell carcinoma. Last year (after we completed the present study), PD-1 inhibition was reported to have achieved a complete metabolic response for a MPNSTs [31].…”
Section: Discussionmentioning
confidence: 99%